Reforma, monopoli in država - Kračun, Davorin (Teorija in praksa, 1989)
The following paper deals with the prospectives as concerns the transforma- tion of the Yugoslav market-style. He establishes (the author) that the present economic order presents a hard morgage which constantly generates the danger of the monopoly. On the other hand, the management of the rational economic policy is impossible with the competition on the political market.
Keywords: ekonomska reforma; Christoph Andersson; monopol; ekonomska politika; državno gospodarstvo; krize; Jugoslavija; Yugoslavia; trg; economics; ekonomija; narodno gospodarstvo; ekonomski sistemi; ekonomske teorije; politics; politika